(untitled) (Italian Journal of Public Health, 2005)
The Italian National Health Care Service, as many other industrialised countries’, has to cope with increasing health care needs in spite of the limited resources available. Therefore, it is necessary to assess diagnostic-therapeutic procedures, technologies and organizational standards, in order to allocate the available resources appropriately. Methodologies developed by the area of research known as Health Technology Assessment, provide scien- tific support for the policies that all countries have adopted in order to rationalize, and sometimes to ration, health care services. Within this context Health Technology Assessment plays a key role in establishing appropriate health care policy decisions. If in the past Health Technology Assessment’s areas of applications have involved mainly macro health care policies, HTA’s methods are now becoming imperative also on an organizational level, as a valuable tool to support managerial decisions. This article outlines the 4 year - experience of A. Gemelli University Hospital of applying HTA methodologies.